Microstructural and Electrochemical Analysis of Inorganic and Hybrid Sol Gel Silica Coatings on Al 7075 Alloy: Effect of Additives - Aydin Goktas, Ali; Malayoglu, Ufuk; Malayoglu, Ugur (Asian Journal of Chemistry, 2012)
Inorganic and organic hybrid coatings were deposited on Al 7075 substrate by dip coating in a sol prepared from tetraethoxysilane with and without addition of both boric acid and ormosil. The samples were heat treated at two different temperatures of 120 and 220 ºC. In case of using ormosil coated samples it was necessary to be heat treated at 120 ºC to obtain full coverage of coatings. For this composition a film thickness of 2-3 micron could be reached by repeatedly coating and heat treatment for 5 times, whereas by other compositions a thickness of only about 1 micron could be reached. Microstructures of the films were characterized by SEM and energy dispersive X-ray analyses (EDX). The crystallization behaviour and thermal analysis of the films as well as gels were studied by XRD and DTA. According to electrochemical results the coated samples from the composition with ormosil repeatedly coated and heat treated for five times at 120 ºC showed the best corrosion resistance. However increasing the temperature resulted in occurrence of micro holes defects and in island forms broken of coatings, which caused weakness of corrosion effect. These findings were confirmed with the SEM micrographs of the same samples. On the other hand boron additives exhibited better adherence of the solution to the substrate compared to tetraethoxysilane solution.